Central Bank Secrecy and Money Surprises: International Evidence - Hutchison, Michael; Judd, John P. (The Review of Economics and Statistics, 1992)
The information value of central bank announcements of projected future money growth is shown to depend both on the accuracy of the announcements and the extent to which the announcements themselves are anticipated by the public. The authors construct a new data set on internal Federal Reserve money projections. These projections, which are kept secret while they are in force, are comparable in many important respects to publicly announced Bank of Japan money projections. Using a derivative of the law of iterated projections, the authors estimate the information value of disclosure on the part of the Bank of Japan and the cost of secrecy on the part of the Federal Reserve. They find that the value of the information provided by the Bank of Japan has been small in terms of reducing money surprises, but that disclosure by the Federal Reserve would have significantly reduced money surprises in the United States. Copyright 1992 by MIT Press.